Evaluation of oil palm leaf nutrients affected by Ganoderma disease - Mohd Yunus, Noor Syaheera; Tajudin, Nur Shuhada; Johari, Siti Nurhusna; Rosham Kadiman, Nurin Maisarah (IIUM Press, 2024)
Oil palm is a highly productive crop, yet its growth and yield are significantly influenced by nutrient availability,making leaf analysis essential to evaluate the nutritional status of oil palms. This study assesses the nutrientontent of oil palm leaves in the Felda Chini, plantation in Pahang, where trees are affected by basal stem rot, a common disease caused by Ganoderma boninense. Leaf samples were collected randomly, with five replications, from trees at four severity levels of basal stem rot classified by FELDA based on observable symptoms. The study focused on five key elements potassium (K), calcium (Ca), magnesium (Mg), copper (Cu), zinc (Zn), and manganese (Mn)—analyzed through the wet digestion method and Atomic Absorption Spectroscopy (AAS). Results indicated a significant decrease (p < 0.05) in nutrient concentrations as infection severity increased, with levels for healthy palms compared to severely infected palms as follows: K (1.03 ± 0.06% to 0.65 ± 0.04%), Ca (1.25 ± 0.08% to 0.76 ± 0.06%), Mg (0.60 ± 0.09% to 0.40 ± 0.04%), Zn (97.60 ± 9.2 mg/kg to 85.02 ± 10.6 mg/kg), and Mn (320.36 ± 18.5 mg/kg to 105.05 ± 20.8 mg/kg). The copper concentrations in oil palm leaves from Felda Chini were undetectable. This suggests either that copper levels in the leaves are extremely low or too minimal for detection by the Atomic Absorption Spectrometer (AAS). This research emphasizes the specific nutrient patterns associated with ganoderma infection, highlighting how this pathogen disrupts nutrient dynamics in oil palm. Future studies incorporating soil sampling could further elucidate the connection between soil nutrient availability and leaf nutrient concentration, advancing our understanding of nutrient management and its role in disease resistance. These findings are crucial for designing targeted soil management strategies to support healthy, sustainable growth in Malaysian oil palm plantations